PEACE EDUCATION-BASED SOCIAL SCIENCE LEARNING THROUGH INTER-ETHNIC RELATIONSHIPS TO EMBED CHARACTER EDUCATION - syafrial nur; Syaiful Bahri; Emi Tipuk Lestari (STKIP Singkawang, 2025)
The purpose of this study is the implementation of peace education-based social studies learning through inter-ethnic social relations to instill character education values at SMP N 28 Pontianak City. This empirical study uses a qualitative approach, with the survay method as an instrument in this review. The data collection techniques used were interview and in-depth observation techniques. The data sources of this study are primary and secondary data. Data analysis used is descriptive qualitative data analysis that is by collecting from various relevant sources and discussing descriptively based on the results of observations and interviews.Research Results. The application of social studies based on peace education in this school has succeeded in embedding the value of tolerance, democracy and other character education values in students. Peace education-based social studies learning, being one of the ways used by teachers to be able to understand better the various forms of local cultural values and the meaning contained in each local wisdom of each ethnic group in the school environment as a learning resource. Peace education-based social studies learning by utilizing ethnic pluralism that exists in learners can help students' understanding of the material of Socio-Cultural Diversity in Society.